Smoke effects on the germination of Cerrado species - Motta, Gabriel Schmidt Teixeira [UNESP]; Pilon, Natashi; Fidelis, Alessandra [UNESP]; Kolb, Rosana Marta [UNESP] (Springer Nature, 2024)
Fire is a natural component in tropical open ecosystems. Therefore, species are adapted to and thrive in post-fire conditions. In these fire-prone ecosystems smoke is one of the fire products that can stimulate seed germination. Here, we evaluated if and how smoke influences the germination of 44 Cerrado ground layer species, including grasses, forbs, subshrubs, and shrubs. Specifically, we aimed to answer the following questions: (1) How does smoke affect the germination of the Cerrado ground layer species? (2) Does smoke concentration influence the response? (3) Does this response differ according to growth form? (4) Are there differences in response between savanna and wet grassland communities? Considering all species together, smoke did not affect the germination of the study species. However, we found species having positive or negative responses, depending on the smoke concentration. When considering growth forms, grasses had a reduction in mean germination time. Smoke also reduced the mean germination time of savanna species, whereas, for wet grassland species, there was no effect of smoke. Thus, smoke has an asymmetric effect on cue germination in the Cerrado, depending on the species, growth form, and habitat. This effect can play a role in community post-fire responses, mostly related to faster germination.
Keywords: Fire; Ground layer; Mean germination time; Savanna; Smoke water